(untitled) (Bioresearch Communications, 2023)
Citrus grandis belongs to the Rutaceae family and is a naturally occurring citrus plant. The fractionated crude extracts of C. grandis have been studied for the investigation of its phytochemicals and allowed for the evaluation of biological activities, especially antimicrobial, cytotoxic, and antioxidant activities. At first, we assessed the antibacterial and antifungal properties using the disc diffusion method and conducted cytotoxicity screening using the brine shrimp lethality bioassay. Among the raw extracts, we isolated two compounds named CG-F3-B1 and CG-F3-B2 through column chromatographic separation of the chloroform extract. By comparing their proton NMR spectra with published spectra, we identified the chemical structures of these compounds as Zeylenol and Limonin, respectively. Regarding antibacterial testing, we observed that the methanol soluble fractions and petroleum ether fractions exhibited mild to moderate activity against bacteria. Additionally, the ethyl acetate soluble fraction showed moderate antibacterial activity. In addition, the crude extract displayed moderate antifungal activity against specific fungi. Furthermore, the cytotoxic assay revealed a relevant cytotoxic effect of a crude extract with an LC50 value of 37 μg/ml. The antioxidant activity was determined using the DPPH assay, and the methanol soluble extract exhibited modest antioxidant activity with an IC50 value of 89 μg/ml. Our findings demonstrated that the stem bark fractions and isolated compounds from C. grandis exhibited various promising biological activities, including antibacterial, antifungal, cytotoxic, and antioxidant properties. Bioresearch Commu. 9(2): 1320-1329, 2023 (July)